Risk factors for KPC-producing Klebsiella pneumoniae bacteremia - Tuon, Felipe F. (2012)
The molecular epidemiology of carbapenemase-producing Klebsiella pneumoniae (KPC) has been largely investigated, but limited clinical information is available. A case-control study was performed to evaluate the risk factors for KPC bacteremia in hospitalized patients. Cases were patients with KPC bacteremia and controls were patients with non-KPC bacteremia. A total of 85 patients were included, 18 (21.2%) were KPC, and 67 (78.8%) were non-KPC (40 [59.7%] of them were extended-spectrum beta-lactamase producers). All KPC isolates were type 2 producers. These isolates belong to five distinct clones. Multivariate analysis showed that age (odds ratio [OR], 1.06; 95% confidence interval [CI], 1.02 – 1.11; p = 0.004), presence of mechanical ventilation (OR, 11.1; 95% CI, 1.92 – 63.3; p = 0.007) and fluoroquinolone exposure during hospitalization (OR, 28.9; 95% CI, 1.85 – 454.6; p = 0.02) were independent risk factors for KPC in patients with K. pneumoniae bacteremia. Factors associated with severity of illness, such as age and mechanical ventilation, seem to be the main risks factors for KPC. Fluoroquinolones use might be a risk factor for KPC bacteremia. Further investigations on risk factors for KPC are warranted.